La Información de la Biblioteca de la Universidad de Pinar del Río con el Uso de una Aplicación Distribuida - Chisaguno T., Verónica E. (2008)
The paper is presented conceived developing an application that manages information related to the different processes of the Library of the University of Pinar del Rio able to satisfy, as quickly and effectively as possible, the needs of specialists and end-users of information services. It formed a development team that completed, following the workflow of the Unified Process, on expectations that the system had users caught using different techniques and be able to contextualize the situation of the university before the applications of new technologies in libraries, which allows; facilitate the management of these processes in their daily tasks, besides providing a solution close to what the customer looking for. By the results achieved in developing the application towards the achievement of an automated management processes Library allowing more time for analysis of decisions to make. The paper consists of three chapters spread across the board in describing the particular business and its processes; analysis and selection of methodology and software to use and finally describes the proposed solution. It issued final considerations that are taxed to the development of the Library and incorporated annexes.